ASYMPTOTICALLY DEFERRED STATISTICAL EQUIVALENT FUNCTIONS OF ORDER ? IN AMENABLE SEMIGROUPS - Et, Mikail; Dutta, Hemen; Braha, Naim L. (Amer Inst Mathematical Sciences-Aims, 2024)
The aim of this paper is to study the asymptotic convergence of the sequences. Concretely, we will give the asymptotically statistical convergence of sequences. The asymptotically statistical convergence is studied in many papers including papers [3], [5], [23], [26], [29], [39], [41]. In this paper, we introduce and investigate the concepts of asymptotically deferred statistical equivalent functions of order a and strong asymptotically deferred statistical equivalent functions of order a defined on discrete countable amenable semi groups, which generalizes some of the results known in the literature. This is achieved by introducing the Folner sequences and sequences of non-negative integers. Based on this concept we apply it to the approximation theory, and we have proved the Korovkin type theorem and study the rate of convergence for positive linear operators which are deferred statistically convergent of order a.
Keywords: Folner sequence; amenable semigroup; asymptotically statistical equivalent; deferred statistical convergence